Quantification of cooking organic aerosol in the indoor environment using aerodyne aerosol mass spectrometers. Issue 10 (3rd October 2021) - Katz, Erin F.; Guo, Hongyu; Campuzano-Jost, Pedro; Day, Douglas A.; Brown, Wyatt L.; Boedicker, Erin; Pothier, Matson; Lunderberg, David M.; Patel, Sameer; Patel, Kanan; Hayes, Patrick L.; Avery, Anita; et al.
Abstract: The Aerodyne aerosol mass spectrometer (AMS) is used extensively to study the composition of non-refractory submicron aerosol composition during atmospheric field studies. During two recent studies of indoor environments, HOMEChem and ATHLETIC, the default ambient organic aerosol AMS quantification parameters resulted in a large discrepancy with co-located instruments while sampling cooking organic aerosol (COA). Instruments agreed within uncertainty estimates during all other sampling periods. Assuming a collection efficiency ( CE ) of unity, adjustments to the AMS relative ionization efficiency ( RIE ) were required to reach agreement with co-located instruments. The range of RIECOA observed (ATHLETIC: RIECOA = 4.26–4.96, HOMEChem: RIECOA = 4.70–6.50) was consistent with RIE measured in the laboratory for cooking-specific molecules. These results agree with prior AMS studies which have indicated that more oxidized outdoor ambient organic aerosol has a relatively constant RIE of 1.4 ± 0.3 while more reduced organics have higher RIE . The applicability of a higher RIE was considered for two ambient datasets, and agreement between the AMS and co-located instruments improved when an increased response factor ( RIE × CE ) was applied to positive matrix factorization-derived primary organic aerosol (POA). Based on the observations presented here and the literature, we recommend AMS users consider applying RIECOA =4.2 to source and indoor studies of COA and evaluate a higher POA response factor of the order of ∼1.5 in outdoor studies at urban background sites, and ∼2 at sites impacted by fresh sources. This study aims to improve AMS quantification methodology for reduced POA and highlights the importance of careful intercomparisons in field studies.